An unusual case of hypopituitarism - Anand, Vishal; Singh, Abhishek Pratap; Anand, Aditya; Achari, Vijay (International Journal of Research in Medical Sciences, 2022)
Lymphocytic hypophysitis represents a difficult diagnostic and therapeutic challenge. The clinical presentation of this inflammatory condition may mimic that of a pituitary adenoma with apoplexy. We report a case of a 45 years old male patient with acute adrenal crisis complicating chronic hypopituitarism secondary to lymphocytic hypophysitis. The patient was managed acutely with high dose steroids and supportive measures, and is currently doing well.